Understanding weight stigma in eating disorder treatment: Development and initial validation of a treatment-based stigma scale. (November 2022) - Chen, Crystal; Gonzales, Lauren
Weight stigma is a well-established risk factor for eating disorder pathology, and it is prevalent among healthcare professionals. The current investigation developed and psychometrically validated the Scale for Treatment-based Experiences of Weight Stigma (STEWS) for patient-centered assessment of weight-stigmatizing experiences in eating disorder treatment. Former eating disorder patients ( N = 142) with a body-mass-index greater than 25.0 were recruited via Amazon Mechanical Turk. The STEWS demonstrated good internal consistency, convergent validity with widely used weight stigma scales, and incremental validity in predicting eating disorder symptomatology. The STEWS is the first psychometrically sound instrument for treatment-based weight stigma in eating disorder recovery.